세종시 단설유치원 학부모의 식생활 교육에 대한 인식과 급식만족도 - 안상희(Sang-Hee An); 김명희(Myung-Hee Kim); 장기효(Ki-Hyo Jang); 이제혁(Je-Hyuk Lee) (東아시아食生活學會誌, 2018)
This study was conducted to investigate parent awareness, satisfaction, demands for foodservice and dietary education in public kindergartens in Sejong. A questionnaire survey of 300 parents was conducted from April 17~28, 2008. The greatest advantage of kindergarten foodservice was nutritionally balanced meals (71.1%) and parents obtained information regarding the kindergarten food service through school newsletters (78.4%). Most parents recognized eco-friendly, organic or local food materials and food specialists (dietitians, cooks) in kindergarten. Parents were also well aware of the impact of feeding during kindergarten on child growth. The most difficult part of the education regarding children's eating habits pertained to unbalanced diets, and the reason why the kindergarten needed dietary education was that they affected the correct eating habits. The teaching method most favored was experiential education through cooking activities. Many parents responded positively to participating in parental education, with housewives having greater intention than professionals, civil servants, and office workers to participate (p<0.001). The satisfaction with food service was 4.16 points on average based on a five-point scale. Additionally, satisfaction with the diversity of school meal menus was highest. The average satisfaction with education regarding dietary habits was 3.99, among which satisfaction with personal hygiene before/after eating (hand washing, brushing, etc.) was highest. Nutritionally balanced foods were the most requested. Finally, many subjects said that the requirements of the cooking room were cleanliness and hygienic management of the food preparation equipment and environment. Overall, the results of this survey will help improve the food service and dietary education of public kindergartens in Sejong.